Acute upper and lower gastrointestinal bleeding management in older people taking or not taking anticoagulants: a literature review - Menichelli, Danilo; Gazzaniga, Gianluca; Del Sole, Francesco; Pani, Arianna; Pignatelli, Pasquale; Pastori, Daniele (Frontiers in Medicine, 2024)
Acute upper and lower gastrointestinal (GI) bleeding may be a potential life-threatening event that require prompt recognition and an early effective management, being responsible for a considerable number of hospital admission. Methods. We perform a clinical review to summarize the recent international guidelines helping the physician in clinical practice. Older people are a vulnerable subgroup of patients more prone to developing GI bleeding because of several comorbidities and polypharmacy, especially related to a higher use of antiplatelet and anticoagulant drugs. In addition, older patients may have higher peri-procedural risk that should be evaluated. The recent introduction of reversal strategies may help the management of GI bleeding in this subgroup of patients. In this review, we aim at 1) summarizing the epidemiology and risk factors for upper and lower GI bleedings, 2) describing treatment options with a focus on pharmacodynamic and pharmacokinetic of different proton pump inhibitors and 3) providing an overview of the clinical management with flowcharts for risk stratification and treatment. In conclusion, GI is common in older patients and a quick management may be helpful in reduction of several complications.